EFEKTIVITAS MEDIA POT HITUNG JAGO PENJUMLAHAN (PITUNG JAPEN) UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PENJUMLAHAN SISWA KELAS II - Pramita, Vinonda Ardi; Wulandari, Murfiah Dewi (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2023)
This study aims to determine the effectiveness of the Pot Hitung Jago Penjumlahan (Pitung Japen) media in improving the numeracy skills of grade II students of Al-Hidayah Karanggede Islamic Elementary School. The type of research used in this research is quantitative research with experimental methods using design One-Group Pretest-Posttest Design. This research usespurposive sampling, involving all second-grade students of SD Islam Al-Hidayah Karanggede. The data collection technique in this study is a test. The analysis used in this study is the validity test, reliability test, differential power, level of difficulty, normality test, homogeneity test, and t-test. Based on the analysis that has been carried out in this study, the research results obtained are that there is a significant difference between learning without Pitung Japen media and learning using Pitung Japen, where the average value of students using Pitung Japen is higher than without Pitung Japen. It can be concluded that the use of Pitung Japen media in improving the numeracy skills of grade II students of Al-Hidayah Karanggede Islamic Elementary School.